Pemerolehan Kalimat Majemuk Anak Usia 4;0 Tahun Melalui Kegiatan Bermain - Rasyid Yulianti (Universitas Negeri Padang, 2021)
The purpose of writing this paper is to describe the acquisition of compound sentences for children aged 4:0 through playing activities. Activities of children aged 4:0 years can not be separated from the world of play. Through play, children will interact and communicate spontaneously. The research method used is descriptive qualitative. The research data is the utterances of children aged 4:0 years in the form of clauses or sentences using listening and listening-engagement-conversation techniques with the help of peer tools and notes as data collection techniques. Data analysis was carried out with the emergence of comprehensiveness criteria, namely the elements that were said would be considered as a reflection of competence. The results found were the utterances expressed by children aged 4:0 years were already in sentence form but also found one or two words which were sometimes still related to the previous utterance. Sentences spoken by children aged 4:0 years already exist in the form of compound sentences that are in accordance with the development of the child's age.